4D Printing of Shape‐Memory Semi‐Interpenetrating Polymer Networks Based On Aromatic Heterochain Polymers. Issue 1 (13th September 2021) - Bardakova, Kseniia N.; Kholkhoev, Bato Ch.; Farion, Ivan A.; Epifanov, Evgenii O.; Korkunova, Olga S.; Efremov, Yuri M.; Minaev, Nikita V.; Solovieva, Anna B.; Timashev, Peter S.; Burdukovskii, Vitaliy F.
Abstract: Most of the presently known thermosensitive shape‐memory polymers suitable for 4D printing have insufficient mechanical strength and thermal stability that restricts their potential areas of application. Here, new photosensitive compositions (PSCs) based on aromatic heterochain polymers – poly‐ N, N ′‐( m ‐phenylene)isophthalamide (MPA) or poly‐2, 2′‐( p ‐oxydiphenylene)‐5, 5′‐dibenzimidazole (OPBI) – for DLP printing are proposed. Thermal post‐curing and supercritical carbon dioxide (scCO2 ) are used for post‐processing of the structures. During the scCO2 treatment the removal of unreacted monomeric component ( N, N ‐dimethylacrylamide) and its uncrosslinked oligomers is accompanied by the preservation of the initial degree of crosslinking. The more stable shrinkage is observed for the combined post‐processing method (T°+scCO2 ) in the case of OPBI‐PSC and after the heat treatment for MPA‐PSC specimens. The method of post‐processing and the nature of the heterochain polymer strongly affect the mechanical properties and thermal resistance of the structures. The tensile strength has the maximum value after the thermal post‐treatment (101.1 ± 7.1 and 78.4 ± 5.1 MPa of OPBI‐PSC and MPA‐PSC, respectively). The intense destruction of the materials is observed at 393 and 408 °C for MPA‐PSC and OPBI‐PSC, respectively. Moreover, the 4D‐printed structures exhibit excellent shape memory performance at transition temperatures >100 °C, thus have a great potential for the use in aerospace, robotics, sensorics. Abstract : New photosensitive compositions based on aromatic heterochain polymers for DLP 4D printing are proposed. Thermal post‐curing and supercritical carbon dioxide (scCO2 ) are used for post‐processing of the structures. These structures are characterized by high mechanical strength (the tensile strength is up to 101.1 ± 7.1 MPa), thermal stability (up to 408 °C), excellent shape memory performance at the transition temperatures >100 °C.